Primary neurodevelopmental disorders in detained adolescents: point prevalence and patterns of care - Hales, Heidi (The journal of forensic psychiatry & psychology, 2022)
Limited information is available on the numbers and trajectories of detained young people with Neurodevelopmental Disorders (NDD) disorders. We completed a census in all types of secure establishments for young people from England. From this, we sought to find the point prevalence of Neurodevelopmental Disorders in young people in secure settings. A quarter of 1322 young people in secure care had at least one NDD; for 204 (18.5%) this was a primary diagnosis. The most common primary diagnosis was ADHD, 101 (9%), followed by 55 (5%) young people with LD and 48 (4%) with ASC. All young people with a primary NDD had had contact prior to detention with at least one of the statutory agencies. More of those with a primary NDD were moved to their current secure placement from a secure placement than those young people without. Existing community identification and support for young people with an NDD is insufficient to prevent significant numbers developing a level of challenging behaviour that requires secure provision. The large numbers of such young people, especially young men, who are detained in the YJS is a grave concern.